2022
DOI: 10.3892/etm.2022.11652
|View full text |Cite
|
Sign up to set email alerts
|

Para‑hydroxybenzaldehyde against transient focal cerebral ischemia in rats via mitochondrial preservation

Abstract: Gastrodia elata (GE) Blume has been widely used for thousands of years to treat various central and peripheral nervous disorders. P-hydroxybenzaldehyde (PHBA) is a chemical component of GE. However, its role and mechanism in transient focal cerebral ischemia remain unclear. The present study aimed to investigate the protective effect of PHBA on middle cerebral artery occlusion (MCAO) rats. A total of 56 Sprague-Dawley male rats were randomly divided into control, model, PHBA-high dose (PHBA-H) and PHBA-low dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…1B ). Our previous study examined a pHBA derivative, p-hydroxybenzaldehyde, which comprised a benzene ring and an aldehyde group with a hydroxyl group ( 20 ). Following drug administration, MCAO modelling and reperfusion, the neurological deficit score of rats was evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1B ). Our previous study examined a pHBA derivative, p-hydroxybenzaldehyde, which comprised a benzene ring and an aldehyde group with a hydroxyl group ( 20 ). Following drug administration, MCAO modelling and reperfusion, the neurological deficit score of rats was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that p-hydroxybenzaldehyde, a component of G. elata , can protect MCAO/R rats from oxidation and apoptosis ( 20 ). Compared with the MCAO/R group, p-hydroxybenzaldehyde treatment reduced mitochondrial ROS and malondialdehyde contents, reduced mPTP opening, and decreased Bax and caspase-3 protein expression levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, it has been reported that sitosterol, vanillin, carotene, gastrodin, p-hydroxybenzaldehyde and other components can reduce blood cholesterol, inhibit the formation of cerebral arteriosclerosis, inhibit the excessive accumulation of cholesterol in nerve cells, anti-apoptosis of nerve cells, maintain the homeostasis of neurogliocyte and protect the integrity of blood-brain barrier. [28][29][30][31][32] In the treatment of IS, these components can inhibit the accumulation of cholesterol in nerve cells, regulate the cholesterol transport function of cholesterol transporter NPC1L1 on the cell membrane, reduce the expression levels of Cathepsin B and Caspase-3 and inhibit the apoptosis pathway of Cathepsin B-caspase. kaempferol, curcumin, ferulic acid, epicatechin and other components regulate the phosphorylation level of Akt and Src proteins, [33] prolong the reaction time of PT and APTT, [34] increase the activity of plasma t-PA, [35] decrease the activity of PAI-1, [36] increase the content of intracellular CGMP, [37] antagonistic endothelin, [38] blocking calcium channels, [39] dilating blood vessels, [40] reducing blood viscosity, reducing platelet aggregation, [41] restoring damaged endothelial tissue, [42] enhancing the activity of plasma anticoagulant system, [43] enhancing the activity of fibrinolytic system, [44] improving blood perfusion, [45] thrombolysis, inhibiting thrombosis, activating platelets, [46] reducing the release of platelet inflammatory factors, [47] reducing the density and coverage of platelet accumulation in cerebral thrombosis and other ways to anti-oxidation, anti-inflammation, anti-tumor and neuroprotection and other pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%